Spin-crossover and mesogenic properties of cobalt(ii) and iron(ii) complexes with ligands derived from 2,6-pyridinedicarboxaldehyde and 1-aminoalkanes / Nur Linahafizza Mohd Noor - Mohd Noor, Nur Linahafizza (2015)
This research was focussed on Co(II) and Fe(II) complexes, designed to be thermally stable, magnetic with spin-crossover (SCO) behaviour, and exhibit mesomorphisms. A total of 14 mononuclear octahedral complexes of general formula [M(Ln)2]X2, where M = Co(II), Fe(II), Ln = Schiff bases formed from the condensation reaction between 2,6-pyridinedicarboxaldehyde and linear chain 1-aminoalkanes (CnH2n+1NH2, n = 6, 8, 10, 12, 14, 16), and X = BF4, ClO4, PF6, were successfully prepared by the one-pot method. The structures of these complexes were deduced from CHN microanalyses, ESI-mass spectrometry, FTIR spectroscopy and UV-vis spectroscopy. Their magnetic properties were determined at room temperature by the Gouy method, and for selected complexes at variable temperatures using the SQUID magnetometer. Finally their thermal and mesomorphic properties by thermogravimetry (TGA), differential scanning calorimetry (DSC), and polarising optical microscopy (POM) were measured. Two complexes, specifically [Co(L12)2](BF4)2 and [Fe(L6)2](ClO4)2, were single crystals. At room temperature, all Co(II) complexes with C6-C10 alkyl chain were a mixture of low spin (LS) and high spin (HS), while complexes with C12-C16 alkyl chain were mainly HS. The HS Co(II) complexes showed normal SCO behaviour in the solid state with T½ at almost room temperature. Complexes with larger anions (ClO4 and PF6) contained lower percentages of HS Co(II). All Fe(II) complexes were mainly LS (89 – 99%) at room temperature. There were no correlation between anionic sizes and percentage of LS in these complexes. The decomposition temperatures of these complexes were in the range of 97 oC – 246 oC. Complexes with BF4- ion and long alkyl chains (C12-C16) were mesomorphic with columnar (Col) mesophase.